DEEP-South: Network Construction, Test Runs and Early Results. Issue Volume 10:Issue S318(2015) (1st March 2016) - Moon, Hong-Kyu; Kim, Myung-Jin; Yim, Hong-Suh; Choi, Young-Jun; Bae, Young-Ho; Roh, Dong-Goo; Park, Jintae; Moon, Bora; ,
Abstract: Korea Microlensing Telescope Network (KMTNet) which consists of three identical 1.6 m wide-field telescopes with 18k × 18k CCDs, is the first optical survey system of its kind. The combination of fast optics and the mosaic CCD delivers seeing limited images over a 4 square degrees field of view. The main science goal of KMTNet is the discovery and characterization of exoplanets, yet it also offers various other science applications including DEep Ecliptic Patrol of SOUTHern sky (DEEP-South). The aim of DEEP-South is to discover and characterize asteroids and comets, including Near Earth Objects (NEOs). We started test runs last February after commissioning, and will return to normal operations in October 2015. A summary of early results from the test runs will be presented.